AN EXPLORATION OF LOCAL LITERATURE AS A MEANS OF PROMOTING CULTURAL TOURISM IN HULU SUNGAI SELATAN - Kamariah, Kamariah; Harpriyanti, Haswinda (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This article presents the development of research on local literature and community culture in Hulu Sungai Selatan Regency, focusing on the exploration and preservation of legends and traditional rituals that are still alive within the society. The article aims to document and analyze the local wisdom values contained in folk tales, such as the Legends of Banyu Baulak and Batu Laki and Batu Bini, as well as their role in the social and spiritual life of the community. Through a qualitative approach, this research collects data from interviews, observations, and literature reviews to understand the meaning and relevance of these legends in a modern context. Additionally, this article explores the potential for developing cultural tourism based on local legends, which can raise awareness of the importance of cultural and environmental preservation. Preliminary results show that local literature not only serves as a cultural heritage but also as a tool to empower the community and attract tourist interest. By integrating educational and interactive elements, such as cultural festivals and educational tour packages, it is hoped to increase community participation and attract the attention of younger generations. This report is expected to make a significant contribution to cultural preservation efforts and tourism development in the area, as well as strengthen the cultural identity of the Hulu Sungai Selatan community.